DEVELOPING ANDROID–BASED EDUTRI (E-MODULE TRIGONOMETRY) FOR GRADE X STUDENTS - Livia Nanda Yantie; Novisita Ratu (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2021)
This research and development aimed to develop electronic learning media for teaching trigonometry. The media developed was EDUTRI, an acronym for E-module trigonometry. This research was conducted on students at class XI IPA 1 and XI IPA 2 of SMA Kristen Satya Wacana, consisting of 34 students as research subjects. The research utilized R&D with the ADDIE development model. This model consists of five stages: analysis, design, develop, implement, and evaluate (evaluation). The validity of the product was examined by the experts’ judgement, while the practicality of the e-module media was examined through limited trials using a questionnaire. Then, the product effectiveness was obtained through a one-class trial with a pretest and posttest design. The results were tested using the Paired Samples T Test. The final result of this research was an android-based e-module media for grade X students. Based on the results from media experts and material experts, the android-based learning media was valid with an average score of 98.33%. In addition, the results of the questionnaire from teachers and students found that the media was practical with a score of 98.33%. Finally, the results of the Paired Samples T Test pretest–posttest confirmed that EDUTRI learning media was effective to be used for learning trigonometry, with an average score of 82.4%.